The biochemistry of the metabolic poison propionate 3‐nitronate and its conjugate acid, 3‐nitropropionate. Issue 9 (29th July 2013) - Francis, Kevin; Smitherman, Crystal; Nishino, Shirley F.; Spain, Jim C.; Gadda, Giovanni
Abstract 3‐Nitropropionate (3‐NPA) is a nitro aliphatic compound found in numerous plants and fungi. The nitro compound exists in equilibrium with its conjugate base, propionate 3‐nitronate (P3N) and has a pKa approaching the physiological range of 9.1. Since 1920, more than 30 species of plant and fungi have been identified as producing 3‐NPA as a means of defense from herbivores. Glycoside products containing moieties of 3‐NPA found in parts of the plants most accessible to herbivores can be easily hydrolyzed to free 3‐NPA by bacterial enzymes in the gut of animals. In addition to providing a defense mechanism, the nitro compound is an intermediate in the nitrification process of leguminous plants. The synthesis of 3‐NPA in these plants and fungi is poorly understood. P3N, which readily forms from 3‐NPA at physiological pH, is a potent inhibitor of the key enzyme succinate dehydrogenase in the Krebs cycle and electron transport chain. Inhibition of succinate dehydrogenase in humans and livestock causes neurotoxicity and in some cases death. Several enzymes catalyze the oxidation of 3‐NPA or P3N; all contain a noncovalently bound flavin cofactor and are found in the organisms that produce 3‐NPA. With kcat/Km values of >106 M−1 s−1, nitronate monooxygenases can quickly and efficiently oxidize P3N to malonic semialdehyde as a means of protecting the organism from killing itself. Although it was discovered almost a century ago, the biochemistry and physiological role of 3‐NPA/P3N are just emerging. © 2013 IUBMB Life, 65(9):759–768, 2013